Exploring Assessment Strategies Used to Promote Metacognitive Development in Science Education - Zarepour, Behnaz; Soleimani, Hamid; Sanjari, Mehrshad (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore the assessment strategies employed by secondary science educators in Tehran to promote metacognitive development among students. A qualitative research design was adopted, utilizing semi-structured interviews with 16 secondary science teachers selected through purposive sampling from various schools in Tehran. Data collection continued until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed using thematic analysis, supported by NVivo software, to identify recurring themes and subthemes related to metacognitive assessment practices. Analysis revealed three main themes: (1) assessment as a tool for reflection, including strategies such as self-monitoring, retrospective and predictive thinking, and structured feedback; (2) teacher roles in supporting metacognition, encompassing the design of metacognitive tasks, facilitation of dialogue, modeling reflective behavior, and creating a supportive assessment climate; and (3) student engagement with metacognition, involving ownership of learning, peer-based reflection, cognitive awareness, and the transfer of metacognitive strategies across tasks. Teachers reported using guided reflection sheets, think-alouds, self-assessment checklists, and collaborative discussions to foster metacognitive skills. Challenges included time constraints, curricular pressures, and balancing formative and summative assessment demands. The findings underscore the importance of intentional assessment design, teacher modeling, and supportive classroom environments in fostering metacognitive development in science education. While effective strategies are being implemented, systemic constraints limit broader adoption. Continued professional development and policy support are recommended to empower educators and prioritize metacognitive learning outcomes in science curricula.